1
$\begingroup$

I have

$\int{\frac{2x+1}{x^2+4x+4}}dx$

Factorising the denominator I have

$\int{\frac{2x+1}{(x+2)(x+2)}}dx$

From there I split the top term into two parts to make it easier to integrate

$\int{\frac{2x+1}{(x+2)(x+2)}}dx$ = $\int{\frac{A}{(x+2)}+\frac{B}{(x+2)}}dx$

=$\int{\frac{A(x+2)}{(x+2)^2}+\frac{B(x+2)}{(x+2)^2}}dx$

Therefore

$2x+1 = A(x+2) +B(x+2)$

This is where I would normally use a substitution method to eliminate either the A term or B term by letting x = something like -2, which would get rid of the A and usually leave me with the B term to solve. However since they are the same I'm not sure what to do.

I've been told to try evaluate the co-efficients, but am not sure how.

$\endgroup$
2
$\begingroup$

You want to try a split like

$$\frac{2 x+1}{(x+2)^2} = \frac{A}{x+2} + \frac{B x}{(x+2)^2}$$

Then $A+B=2$ and $2 A=1$. The decomposition is then

$$\frac{2 x+1}{(x+2)^2} = \frac12 \frac1{x+2} + \frac{3}{2} \frac{x}{(x+2)^2}$$

$\endgroup$
  • $\begingroup$ Is it $Bx$? I doubt $\endgroup$ – Semsem Apr 6 '14 at 9:06
  • $\begingroup$ @semsem: you doubt what? Check the work, it is correct. I could have done just $B$ as well. The reason either way works is that one may add and subtract $2$ in the numerator of the second fraction to change the representation. $\endgroup$ – Ron Gordon Apr 6 '14 at 9:12
  • $\begingroup$ Ok, you are right $\endgroup$ – Semsem Apr 6 '14 at 9:13
4
$\begingroup$

Hint

$$\int{\frac{2x+1\color{red}{+3-3}}{x^2+4x+4}}dx=2\ln|x+2|+\frac{3}{x+2}+C$$

$\endgroup$
  • $\begingroup$ This is the best what can be done. $\endgroup$ – kmitov Apr 6 '14 at 8:47
1
$\begingroup$

All you need to do is to solve this with respect to polynomials:

$2x+1=Ax+2A+Bx+2B$

$2x+1=x(A+B)+(2A+2B)$

$A+B=2 \rightarrow B=2-A$

$2A+2B=1$

$2A+4-2A=1\rightarrow 4=1$

This is contradiction! You have made an mistake in step where you split the term into two fractions, you should have done it like this:

$\frac{2x+1}{(x+2)^2}=\frac{A}{x+2}+\frac{B}{(x+2)^2}$

and then proceed like usual.

$A(x+2)+B=2x+1$

$A=2$

$2A+B=1$

$B=-3$

$\int \frac{2}{x+2}+\frac{-3}{(x+2)^2}dx=2ln(x+2)+\frac{3}{x+2}+C$

$\endgroup$
1
$\begingroup$

In this case we a linear repeated factor so we split it like $$\frac{A}{(x+2)}+\frac{B}{(x+2)^2}=\frac{A(x+2)+B}{(x+2)^2}$$ and hence $$2x+1=A(x+2)+B=Ax+2A+B$$ then by equating coefficients $$A=2,\\2A+B=1\implies B=-3$$

$\endgroup$
  • $\begingroup$ How did you get A=2 from that? $\endgroup$ – user88720 Apr 9 '14 at 6:14
  • $\begingroup$ @user88720 i edited it $\endgroup$ – Semsem Apr 9 '14 at 7:07

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.